OPTIMIZATION OF APRON MOVEMENT CONTROL (AMC) SERVICES AT THE APRON OF HANG NADIM INTERNATIONAL AIRPORT BATAM - Jaehar, Fikri Amal; Ratna Sari, Dewi; Furyanto, Faoyan Agus (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Hang Nadim Batam International Airport is an airport managed by PT BIB which is located in the city of Batam, Riau Islands. In operational activities on the apron, AMC officers still experience problems in the form of fuel/oil spills from aircraft and groundhandling GSE vehicles. The spill made the apron dirty. So it is necessary to improve services or optimize operations on the apron so that the apron is always maintained in a clean condition. The method in this research uses descriptive qualitative using data collection techniques in the form of interviews, observation and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of this research concluded that AMC's operational services on the apron were in the form of aircraft parking plotting, apron cleanliness, aerobridge services, and follow-me car services. Efforts made by AMC to address existing obstacles are creating a Service Level Agreement (SLA) so that AMC services on the apron of Batam's Hang Nadim International Airport are optimal.